BONE REGENERATION AFTER IMPLANTATION OF CALCIUM PHOSPHATE CEMENTS BASED ON METASTABLE TRICALCIUM PHOSPHATE (IN VIVO EXPERIMENTAL STUDY) - Poplavska, Karolina; Ashukina, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Calcium phosphatCalcium phosphate cement (CPC) is a material used to fill bone defects. Its advantages include being able to fill irregularly shaped spaces, its similarity to bone tissue, and ease of biodegradation. However, insufficient durability and unpredictable rate of resorption limit CPC use. Objective. Study the dynamics of morphological changes in rat femurs after implanting two types of CPC based on metastable αʹ‒tricalcium phosphate (αʹ‒TCP) into defects in the distal metaphysis. Methods. 42 male white rats were used in the study. In each rat, defects were created in the distal metaphysis of the left femur and filled with one of the two types of CPC. The animals were split into two groups: І (n = 21) — CPC based on αʹ‒TCP powder; ІІ (n = 21) — CPС based on αʹ‒TCP powder reinforced with hydroxyapatite (HA) whiskers (4 % mass). Both varieties of CPC were developed and prepared at the Department of Solid-State Physics at the V. N. Karazin Kharkiv National University (Ukraine). 14, 30, and 60 days after the surgery, the animals were sacrificed, and histological analyses were performed. Results. For both types of CPC, inflammation was not observed in the region around the implant at 14, 30, or at 60 days. Bone tissue formed on the surface of the materials. The stages of bone repair were similar to the known stages of bone repair. As a result of the resorption of the CPC, 60 days after surgery the CPC comprised 26.83 % of the area of the defect in group I and 29.93 % in group II. The rest of the area was composed of lamellar bone. The two groups did not differ significantly in rate of CPC resorption or bone tissue formation. Conclusions. The two types of CPC studied, based on αʹ‒TCP (group I) and αʹ‒TCP reinforced with HA whiskers (group II), are biocompatible, osteoconductive, and osteoinductive. In addition, these materials are biodegradable and, with time, are replaced by bone tissue.